Community Capitals: Poverty Reduction and Rural Development in Dry Areas - Flora, Cornelia Butler; Thiboumery, Arion (Annals of Arid Zone, 2016)
The lack of water in communities in arid lands is often related to the mal-distribution or absence of other resources. In the past, many communities responded to scarce resources by transhumance, building on cultural capital and social capital to produce sustainable livelihoods. But lack of political capital has reduced the options of transhumant communities. As they settle, new pressures are put on natural capital, beginning a downward spiral of other community resources. Successful efforts to reduce poverty in arid lands invest in many capitals in order to reverse the spiraL Attention to bridging and bonding social capital as an entry to poverty reduction is often more successful than built capital to provide bore holes or wells. Attention to cultural, human, social, and political, as well as natural, financial and built, is required for sustainable development in arid lands.